Peningkatan Kemampuan Difabel Melalui Pelatihan Bending Bambu Di SLB Paedagogia Maospati Kabupaten Magetan - Setio Hastorahmanto, Stefan Prabani; Widyastuti, Maria; WS Panjaitan, Thyophoida; Silfira; Frumensia; Hawa (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
The abilities of the disabled develop in a good direction if training and coaching are carried out routinely. Training provides motor and logic skills, coaching provides the right direction. The disabled find it difficult to take the initiative, tend to be withdrawn and unfocused. Collaboration between the disabled and non-disabled creates synergy and produces work that can be proud of. The pride of the disabled is seen when they are able to produce work. Self-confidence, enthusiasm for life and optimism will increase. They feel useful to others. SLB Paedagogia Maospati Magetan is an inclusive school for the disabled. All disabled students can receive basic education, skills and therapy for recovery. This SLB has become a partner of Darma Cendika Catholic University - Surabaya as a place for Community Service (PkM). Empowerment is directed at training students in wood craft skills with bending techniques through the lamination process. In 2021, they were trained to make simple tables and chairs with plywood material. In 2022, the making of backrest chairs continued. In 2024, training was increased for greater difficulties. Through the method of Practice and direct supervision, following the SOP set in the production process and directed to understand the work of the industry. The use of materials using bamboo. Through collaboration, disabled and non-disabled work is able to produce work. This training shows: 1) disabled people will try to follow and adjust the applied SOP; 2) The success of the work provides enthusiasm, hope and confidence.